INTEGRATED CARE FOR THOSE WITH LUNG DISEASE - Partridge, Martyn R (Journal of Postgraduate Medical Institute, 2016)
Integrated care may be defined as "the best possible care for the patient, delivered by the most suitable health professional, at the optimal time, in the most suitable setting". The current interest in the subject of integrated care has come about largely because of the unplanned fragmentation of care which has occurred in many health care systems over the last two decades; and secondly because it represents the most effective patient centred manner in which to provide healthcare.